The E.R.P. and the problems of Italian agriculture - MEDICI, G. (PSL Quarterly Review, 2014)
The article analyses some aspects of Italian agriculture, as seen in the framework of national economy: the congestion of the agricultural population, the relations between agriculture and industry, the structure and forms of land tenure, the importance of the agricultural trade balance for international trade as a whole. The author illustrates the main lines that agricultural development should follow in the next few years if a general increase of production is to be secured and insists on the need of taking immediate steps towards the solution of the more important problems facing Italian agriculture by a wise use of the E.R.Ps Funds. Special stress is laid on the need of increasing the production of fresh fruit and vegetables and the products of animal husbandry; on the execution of land reclamation and irrigation works; the improvements of conditions in mountain areas; the mechanisation of agriculture; agricultural training for the peasantry; experiment stations and research work; the organisation of agricultural producers; and the strengthening of agrarian credit. JEL: O13, Q15, Q17